Dire Straits-Education Reforms Ideology, Vested Interests and Evidence - Gomendio, Montserrat (Open Book Publishers, 2023)
Responding to an 'educational emergency' generated largely by the difficulties of implementing education reforms, this book compares education policies around the world in order to understand what works where. To address the key question of why education reforms are so difficult, the authors take into account a broad range of relevant factors, such as governance, ideology, and stakeholder conflicts of interest, and their interactions with one another. Drawing on their experiences as policymakers in the Spanish government and as governmental advisors worldwide, Montserrat Gomendio and Jose Ignacio Wert produce a publication like no other, shifting the usual Eurocentric narrative and shedding light on frequently overlooked educational policies from elsewhere. In this context, they dive deeper into details of educational failures and successes, the processes of implementation and investment priorities in different countries. They provide revealing accounts of stakeholder conflicts of interest and the challenges of implementing educational reform during a financial crisis. The authors also investigate why the evidence from international large-scale assessments (ILSAs) has, contrary to expectation, not generated improvements in most education systems. Gomendio and Wert investigate the evolution of different education systems, closely examining their advances or declines. Gomendio and Wert's expert voices illuminate the current state of global education systems and the necessary changes to ensure long-awaited improvements. This is a revelatory and informative resource for policymakers, teachers and academics alike.